(untitled) - Dr. Jan Busse, Universität der Bundeswehr München; Prof. Dr. Bernhard Stahl, Universität Passau (ZIB Zeitschrift für Internationale Beziehungen, 2023)
Zeitschrift für Internationale Beziehungen (ZIB) is the flagship journal of the German International Relations community. According to a poll amongst German political scientists across various sub-fields conducted in 2009 it is also considered the best German-language journal in Political Science at large. ZIB publishes articles that make original as well as theoretically and methodically reflected contributions to the study of international relations. The thematic spectrum includes the entire range of IR, including IR theory, foreign policy analysis, international institutions, peace and conflict resolution, security policy, European integration, North-South relations, development policy, and international economic relations. The high quality of articles that are published in ZIB is ensured through  double blind peer review. ZIB was the first journal in German Political Science to introduce such a process. Since its founding in 1994 ZIB has greatly contributed to the professionalization of the German IR-community and can be considered a key source for thematic stimuli on theoretical, methodological and empirical levels at the edge of contemporary IR research. Website: www.zib.nomos.de